2008 International Conference on Intelligent Sensors, Sensor Networks and Information Processing 2008
DOI: 10.1109/issnip.2008.4761970
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting model for crude oil prices based on artificial neural networks

Abstract: This paper presents short-term forecasting model for crude oil prices based on three layer feedforward neural network. Careful attention was paid on finding the optimal network structure. Moreover, a number of features were tested as an inputs such as crude oil futures prices, dollar index, gold spot price, heating oil spot price and S&P 500 index. The results show that with adequate network design and appropriate selection of the training inputs, feedforward networks are capable of forecasting noisy time seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 15 publications
0
23
0
2
Order By: Relevance
“…The neural network arbitrage strategy focuses on the research object's volatility, thus making arbitrage strategies. Haider et al (2008) [14] used artificial neural network model to predict the oil futures market, and found that using artificial neural network to develop arbitrage strategy could help to improve the yield. Phoebe and David (2014) [15] using the RBF neural network, LM neural network model for soybean meal, soybean oil, soybean and its squeezing goods spread analysis predicted the short-term fluctuations, thinking that traders could according to the forward contracts affected the recent contract squeezing spreads profit carry this phenomenon.…”
Section: Advances In Computer Science Research Volume 82mentioning
confidence: 99%
“…The neural network arbitrage strategy focuses on the research object's volatility, thus making arbitrage strategies. Haider et al (2008) [14] used artificial neural network model to predict the oil futures market, and found that using artificial neural network to develop arbitrage strategy could help to improve the yield. Phoebe and David (2014) [15] using the RBF neural network, LM neural network model for soybean meal, soybean oil, soybean and its squeezing goods spread analysis predicted the short-term fluctuations, thinking that traders could according to the forward contracts affected the recent contract squeezing spreads profit carry this phenomenon.…”
Section: Advances In Computer Science Research Volume 82mentioning
confidence: 99%
“…The main reason is attributed to the irregularity and the sudden abrupt changes in the oil price behavior that marked the last three decades [19]. Specifically, the prediction will inevitably be incomplete, as the network representation of the relationships between oil prices and the respective factors require an explicit mapping [20].…”
Section: Feature Selection For Forecastingmentioning
confidence: 99%
“…Crude oil prices prediction is not an easy task because there are many factors that can influence their tendency such government interventions, political events, weather conditions, financial speculations, supply, inventories, demand, exchange rates, OPEC oil policy, GDP, financial shocks, price trends and stock market, dollar index, gold, heating oil spot price, etc. [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Some machine learning methods such as artificial neural networks (ANNs) and support vector machines (SVM) were proposed to solve the nonlinearity problems of time series and gave better results than conventional methods. For example, many researchers applied ANN based models [11][12][13][14]. Pierdzioch et al [15,16] forecasted oil price under asymmetric loss and found new evidence of anti-herding of oil price forecasters.…”
Section: Introductionmentioning
confidence: 99%